THE PATHOMORPHOLOGICAL SIGNS OF APPENDICITIS IN CHILDHOOD - Farmonova Rukhshona Farrukhovna,; Norjigitov Azamat Musakulovuch, (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
Annotation. Appendicitis is a pathological process in which inflammation of the appendix, located at the border of the colon and small intestines, occurs. This disease can occurs at any age and can only be treated surgically. It is important to remember that without the help of a doctor, the pathological process leads to peritonitis (inflammatory process in peritoneum layer) and even fatal outcome. According to the literature, acute appendicitis under the age of 1 year is extremely rare and ranges from 0.06 % to 0.2 %.